A guide to choosing fluorescent protein combinations for flow cytometric analysis based on spectral overlap. Issue 5 (13th March 2018) - Kleeman, Benjamin; Olsson, Andre; Newkold, Tess; Kofron, Matt; DeLay, Monica; Hildeman, David; Grimes, H. Leighton
Abstract: The advent of facile genome engineering technologies has made the generation of knock‐in gene‐expression or fusion‐protein reporters more tractable. Fluorescent protein labeling of specific genes combined with surface marker profiling can more specifically identify a cell population. However, the question of which fluorescent proteins to utilize to generate reporter constructs is made difficult by the number of candidate proteins and the lack of updated experimental data on newer fluorescent proteins. Compounding this problem, most fluorescent proteins are designed and tested for use in microscopy. To address this, we cloned and characterized the detection sensitivity, spectral overlap, and spillover spreading of 13 monomeric fluorescent proteins to determine utility in multicolor panels. We identified a group of five fluorescent proteins with high signal to noise ratio, minimal spectral overlap, and low spillover spreading making them compatible for multicolor experiments. Specifically, generating reporters with combinations of three of these proteins would allow efficient measurements even at low‐level expression. Because the proteins are monomeric, they could function either as gene‐expression or as fusion‐protein reporters. Additionally, this approach can be generalized as new fluorescent proteins are developed to determine their usefulness in multicolor panels. © 2018 International Society for Advancement of Cytometry